Political Recruitment and Party Institutionalization: PDIP's Internal Tension in the 2020 Surakarta Mayoral Election - Sulaksono, Tunjung; Sungkawa, Janur Dikya; Suswanta, Suswanta; Sutan, Arissy Jorgi (Universitas Muhammadiyah Malang, 2023)
This article aims to explain the causes of internal tension within the Indonesian Democratic Party—Struggle (PDIP) Party. The internal tension occurred vertically and horizontally due to the party’s central office intervention in the recruitment process for the 2020 Surakarta mayoral candidate. The intervention caused disappointment among Surakarta Branch Leadership Council (DPC) Surakarta cadres towards the PDIP's Central Leadership Council (DPP) policies and deconsolidation within the DPC level prior to the election. The research approach used is descriptive-qualitative, with data collection techniques used are documentary and literature studies. In contrast to the explanation of previous works that emphasize the oligarchy and centralism of decision-making, this article shows that the cause of the internal tension within the PDIP Party is the low degree of party institutionalization, especially in the systemness and decisional autonomy dimensions.